2015
DOI: 10.1111/1365-2745.12503
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of flammability in savanna grass species

Abstract: Summary Tropical grasses fuel the majority of fires on Earth. In fire‐prone landscapes, enhanced flammability may be adaptive for grasses via the maintenance of an open canopy and an increase in spatiotemporal opportunities for recruitment and regeneration. In addition, by burning intensely but briefly, high flammability may protect resprouting buds from lethal temperatures. Despite these potential benefits of high flammability to fire‐prone grasses, variation in flammability among grass species, and how trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(201 citation statements)
references
References 65 publications
8
190
0
3
Order By: Relevance
“…This was similar to other findings that an open litter bed structure with low bulk density burns more rapidly than tightly packed ones (Scarff & Westoby, ; Cornwell et al ., ). Grass flammability is affected by canopy architecture (Simpson et al ., ) and in our experiment, grass fuels were laid horizontally, with no major gaps, unlike the more variable, generally vertical arrangement of grasses in the field. [Other researchers have similarly placed shoots horizontally to measure shoot flammability (Jaureguiberry et al ., ; Wyse et al ., )].…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to other findings that an open litter bed structure with low bulk density burns more rapidly than tightly packed ones (Scarff & Westoby, ; Cornwell et al ., ). Grass flammability is affected by canopy architecture (Simpson et al ., ) and in our experiment, grass fuels were laid horizontally, with no major gaps, unlike the more variable, generally vertical arrangement of grasses in the field. [Other researchers have similarly placed shoots horizontally to measure shoot flammability (Jaureguiberry et al ., ; Wyse et al ., )].…”
Section: Discussionmentioning
confidence: 99%
“…However, grasses are not homogeneous fuels to fire. A recent study on the flammability of grasses from South African fire-prone environments showed different degrees of flammability driven by different functional traits and ultimately by evolutionary history [79]. Finally, regeneration will depend on the ability of the already established vegetation to persist after fire by resprouting, or by favouring new individuals to germinate (e.g.…”
Section: (B) Firementioning
confidence: 99%
“…Its height and rapid growth enable T. triandra to out compete neighbouring species for light, water and nutrients. Fire also plays an important role in its dominance, with T. triandra being highly flammable relative to co-occurring grass species (Simpson et al 2016) and its persistence reliant on burning (Danckwerts 1993). These characteristics are, however, at least partially shared across the genus (Morales 2014).…”
Section: Genome-wide Nuclear Phylogenymentioning
confidence: 99%
“…Establishing why savannas are dominated by relatively few species requires considering the origins of the grass species that dominate these habitats, in terms of space, time and ancestral conditions. Among C 4 grass species, variation in flammability is phylogenetically constrained, and the traits of the grassy ground layer have ecosystem-level impacts on fire frequency and intensity (Archibald et al 2013;Simpson et al 2016). A key question is therefore whether grass traits underlying savanna dynamics existed before the colonisation of these ecosystems, or whether they evolved in situ.…”
Section: Introductionmentioning
confidence: 99%